Improved creep resistance of high entropy transition metal carbides. Issue 7 (July 2020) - Han, Xuxu; Girman, Vladimir; Sedlak, Richard; Dusza, Jan; Castle, Elinor G; Wang, Yichen.; Reece, Mike; Zhang, Chengyu
Abstract: The creep behaviour of (Ta-Hf-Zr-Nb)C high entropy ceramic (HEC) was investigated at temperatures between 1400 and 1600 °C in vacuum under compressive stresses from 150 to 300 MPa. The measured steady-state creep rates ranged from 2 × 10 −9 /s to 8 × 10 -8 /s, which are approximately 10 times lower than the published creep rates of the corresponding monocarbides. The stress exponent n is in the range of 2.34 ∼ 2.89 and the average activation energy is 212 kJ/mol. The creep mechanisms involve dislocation glide/climb and the formation of voids and cracks. The voids formed at the grain boundaries parallel to the loading direction, which often connected to form cracks at the highest load/temperature The active dislocation slip system during creep was &lt, 110&gt, {111}. The reason why (Ta-Hf-Zr-Nb)C has enhanced creep resistance compared to the monocarbides can be explained by lattice distortion and the higher thermodynamic stability of HEC ceramic at high temperatures.